ENGLISH Comparative Literature in the Digital Age: Re-reading Classical Islamic Texts through Digital Humanities - Dr. Naseem Akhter; Dr. Amjad Hayat (Rahat-ul-Quloob, 2020)
This article critically examines the impact of digital humanities on the field of comparative literature, specifically in the provision of new reading and interpretation modes for classical Islamic texts. Islamic literary and religious works are traditionally studied in theological or philological paradigms, but are currently made more available through online-based digital libraries, electronic manuscript archives, and multilingual database systems. Such developments inspire comparative interactions of world literatures that cut across traditional boundaries of language, space and genre. The article is located in the broad field of comparative literature, where classical Islamic literature (narratives in the Holy Quran and classical adab literature) is focused on the significance of digital technologies in supporting cross-cultural and intertextual readings. The research challenges the reinvention of meaning, authority as an author and as an interpreter in the digital age through the deployment of digital methodologies, such as textual mapping, corpus-based comparison, and hyper-textual reading. This article continues to question important issues of authenticity, ethical regard and scholarly responsibility that are introduced by the mediation of sacred and classical texts using digital media. Using limited comparative examples, the article illustrates how far digital humanities can expand the scope of comparative literature, on the one hand, and protect the intellectual and ethical integrity of the tradition of the Islamic texts, on the other hand. Finally, the article argues that the incorporation of digital humanities fosters future prospects of comparative literature by building upstream and methodology-driven and globally networked scholarship.